(untitled) (Research, Society and Development, 2021)
This work’s main goal was to establish, from qualitative research, criteria and weigth applicable to the selection process of wastewater treatment systems, a process that usually involves a many criteria and differents environmental, operational, economic and social aspects. Nineteen criteria were considered, distributed among four socio-technical subsystems. The Environmental Subsystem was the most relevant for selection process. Removal organic matter efficiency, removal coliforms efficiency and energy demand were considered the most important criteria by specialists. Interference of aerosols generation and the possibility of insect attraction, criteria associated to the Social Subsystem, were considered as the least important criteria.